Pengaruh Selfesteem, Adaptabilitas Karir terhadap Kinerja Karyawan dengan Perceived Organizational Support sebagai Variabel Mediasi: Studi Kasus: Karyawan Bank Sumut Syariah KC Kota Padangsidempuan - Fauziah, Isna; Anggraini, Tuti; Harahap, Rahmat Daim (Ikatan Da'i Indonesia, 2023)
This research aims to determine the effect of self-esteem, career adaptability on employee performance with perceived organizational support as a mediating variable. The population of this research is employees of PT. Bank Sumut Syariah KC Padangsidimpuan City. The sample size was 30 people taken based on non-probability sampling. The questionnaire is a data collection tool used in this research, while the type is quantitative research. The data analysis technique uses path analysis with the SPSS Version 22 program. The findings of this research are 1) self-esteem has a positive and significant effect on perceived organizational support. 2) career adaptability has a positive and significant effect on perceived organizational support. 3) self-esteem has a positive and significant effect on performance. 4) career adaptability has a positive and significant effect on performance. 5) perceived organizational support has a positive and significant effect on performance. 6) self-esteem does not have a positive and significant effect on employee performance through perceived organizational support. 7) self-esteem does not have a positive and significant effect on performance through perceived organizational support at PT. Bank Sumut Syariah KC Padangsidimpuan.